Diagnosis of an Additional Ventricular Septal Defect by Observing Dark Blood in Aortic Root Vent: A Case Report. Issue 2 (15th July 2019) - Babu, Saravana; Gadhinglajkar, Shrinivas; Sreedhar, Rupa; Nemani, Nayana; Sukesan, Subin; Baruah, Sudip Dutta
Abstract : Diagnosis and management of multiple ventricular septal defects still remain a challenging task. Although many new diagnostic modalities have been used for the perioperative diagnosis of ventricular septal defects, the discovery of residual or additional shunts in the postoperative period is not uncommon. We report a case where we observed an undiagnosed additional ventricular septal defect shunting deoxygenated dark blood into the aortic root vent during deairing of the heart, which was confirmed on transesophageal echocardiography and addressed with reinstitution of cardiopulmonary bypass.